TIZANIDINE IN THE MANAGEMENT OF MUSCULOSKELETAL PAIN, WITH PARTICULAR EMPHASIS ON BACK PAIN: MECHANISM OF ACTION, EFFICACY, SAFETY, AND CLINICAL USE – A LITERATURE REVIEW - Krystian Kaczmarek; Wiktoria Zawada; Zofia Jadwiga Leszczyńska; Vladyslav Romaniuk; Urszula Szuleta; Agnieszka Benecka; Jakub Pietrończyk; Alicja Benecka; Zuzanna Wieczorek; Iga Tartas; Natalia Prankiewicz (International Journal of Innovative Technologies in Social Science, 2026)
Musculoskeletal pain, including back pain, is a leading cause of disability worldwide and often coexists with increased paraspinal muscle tension and painful muscle spasm. This narrative review aimed to summarize current knowledge on the mechanism of action, clinical efficacy, safety profile, and clinical use of tizanidine in musculoskeletal pain, with particular emphasis on back pain. The review included clinical trials, systematic reviews, case reports, clinical practice guidelines, prescribing information, and toxicological data concerning tizanidine. Tizanidine is a centrally acting alpha-2 adrenergic receptor agonist that inhibits polysynaptic spinal reflexes and exhibits both antispastic and antispasmodic effects, with possible involvement of imidazoline receptors. Earlier studies suggested that adding tizanidine to nonsteroidal anti-inflammatory drugs may improve outcomes in acute low back pain, whereas more recent randomized trials did not confirm additional clinical benefit. The most common adverse effects include drowsiness, dry mouth, hypotension, dizziness, and weakness. Rare but serious adverse effects include hallucinations, bradycardia, hepatotoxicity, and withdrawal symptoms after abrupt discontinuation. Strong CYP1A2 inhibitors, especially ciprofloxacin and fluvoxamine, markedly increase the risk of hypotension and excessive sedation. Evidence on the efficacy of tizanidine remains inconsistent. Tizanidine is not a first-line treatment but may be considered as short-term adjunctive therapy in selected patients when a muscular component is clinically relevant.